Analysis of the sanitation management in the informal settlement Bajo Los Anonos, San José, Costa Rica, from a social, technical and institutional perspective - Rueda Morales, Maryeluz (2018)
Objective: To analyze from a social, technical and institutional perspective the sanitation conditions that currently exist in the informal settlement Bajo Los Anonos located in San José, Costa Rica. Methods: By applying surveys to the inhabitants of the place, it was made a technical and social characterization of the self-management of sanitation in the community; in addition, it was realized a simple sampling of wastewater in three different points of the community; finally, we made a survey with open questions to the environmental manager of the Municipality of Escazú to know their perspective. Results: Although 82% agreed that poor wastewater management is one of the main problems, more than half of the people did not find a relationship between the level of sanitation and its interference in health. Transit of wastewater in the streets exposes the population to a level of risk. Even though the Municipality of Escazú is aware of the problem, there are no clear plans for the community. Conclusions: The community presents problems regarding the correct management of wastewater, due to a combination of factors, such as lack of access to quality sanitation systems, bad practices of neighbors and lack of institutional support.